Animal health and productivity among dairy cattle in Bihar, India - Hannfors, A. (Swedish University of Agricultural Sciences, 2016)
Bihar lies in the north of India and is one of the poorest states in the country. Agriculture is very important in the local economy and the contribution of animal husbandry, where dairy animals are the most common, is considerable. A majority of dairy farmers are poor smallholder, to whom milk production is important both as a source of additional income as well as being a source of important nutrients to the farmers family. Milk yield per animal in Bihar has however been low compared to the rest of the country because of problems with disease, reproduction and animal management. The aim for this study was to investigate general animal health and management in dairy cattle, to identify ways to improve the milk yield of animals to improve the situation of local farmers. Factors included and registered in the study were related to animal management and health, and included milk yield, body condition scoring (BCS) and feed, water intake and hoof health and lameness. Data was collected through clinical examinations of individual animals and through the use of a questionnaire. A total of 229 households and 342 individual animals were included in the study. Dominance of smallholders in Bihar was verified in the study, with a mean of 3.5 animals per household, and an absolute majority of the animals surveyed were crossbred. Mean daily milk yield per animal in households was 8.3 L/day. Body condition and rumen fill were both found to be within adequate ranges, indicating a satisfactory energy intake for animals. Both inclusion of concentrate in the feed of animals and increased intake of water was found to be associated with a significant increase in milk yield. Inclusion of concentrates in feed led to an increase of 1.78 L/day in mean daily milk yield, and for every additional liter of water, mean daily milk yield increased by 0.1 L/day. Hoof status of surveyed animals was found to be normal in an absolute majority of cases, and the annual incidence rate of lameness was found to be extremely low when compared to previous studies. In conclusion, adequate BCS, rumen fill and good hoof status indicates a good general health of animals in Bihar. The good hoof status and low incidence rate of lameness indicate that hoof related lesions are not a major problem in the state. Proportion of crossbred animals and the daily milk yield of animals seem to be higher as compared to previous studies from Bihar, and a potential of increased milk yield through an increase of water intake as well as from inclusion of concentrates in the feed is shown. Further research would however be needed to verify the results of this study.